Beauty, virtue, and religious exemplars. Issue 2 (28th December 2015) - KIDD, IAN JAMES
Abstract: This article explores the beauty of religious exemplars – those special persons whose conduct and comportment marks their life out as one that exemplifies a religious life. Such exemplars are consistently described as beautiful, but it is not clear how or why. I suggest that we can make sense of the aesthetic aspect of religious exemplarity by adopting a 'virtue-centric' theory of beauty that understands the beautiful in terms of the expression or manifestation of virtues. Religious exemplars are those who have cultivated their virtues to an advanced degree and are beautiful for that reason. Attending to the beauty of religious exemplars can enrich exemplarist virtue theory, the aesthetics of character, and our understanding of the nature of a religious life.